Simultaneous electrochemical detection of dopamine and uric acid via Au@Cu-metal organic framework - Zhou, Feng; Lim, H. N.; Ibrahim, I.; Endot, N. A.; Malek, E. A.; Gowthaman, N. S. K. (Wiley, 2024)
The incorporation of noble metals with metal-organic frameworks (MOFs) are conducive to the simultaneous electrochemical detection of analytes owing to multiple accessible reaction sites. Herein, Au@Cu-metal organic framework (Au@Cu-MOF) is successfully synthesized and modified as a screen-printed carbon electrode (SPCE), which serves as an excellent electrocatalyst for the oxidation of dopamine (DA) and uric acid (UA). The sensor shows a linear range from 10 μM to 1000 μM, with sensitivity and detection limit of 0.231 μA μM−1 cm−2 and 3.40 μM for DA, and 0.275 μA μM−1 cm−2 and 10.36 μM for UA. Au@Cu-MOF could realize the individual and simultaneous electrochemical sensing of DA and UA, with distinguishable oxidation peak potentials. Moreover, it exhibits reproducibility, repeatability, and stability. Ultimately, the sensor provides an avenue for an ultrasensitive label-free electrochemical detection of DA and UA.